Difference between revisions of "2005 AIME I Problems/Problem 12"
m |
(breakup huge equation, which is showing up poorly on my screen, box, alternative) |
||
Line 6: | Line 6: | ||
So, for a given <math>n</math>, if we choose the positive integer <math>m</math> such that <math>m^2 \leq n < (m + 1)^2</math> we see that <math>S(n)</math> has the same parity as <math>m</math>. | So, for a given <math>n</math>, if we choose the positive integer <math>m</math> such that <math>m^2 \leq n < (m + 1)^2</math> we see that <math>S(n)</math> has the same parity as <math>m</math>. | ||
− | |||
It follows that the numbers between <math>1^2</math> and <math>2^2</math>, between <math>3^2</math> and <math>4^2</math>, and so on, all the way up to the numbers between <math>43^2</math> and <math>44^2 = 1936</math> have <math>S(n)</math> odd, and that these are the only such numbers less than <math>2005</math> (because <math>45^2 = 2025 > 2005</math>). | It follows that the numbers between <math>1^2</math> and <math>2^2</math>, between <math>3^2</math> and <math>4^2</math>, and so on, all the way up to the numbers between <math>43^2</math> and <math>44^2 = 1936</math> have <math>S(n)</math> odd, and that these are the only such numbers less than <math>2005</math> (because <math>45^2 = 2025 > 2005</math>). | ||
Line 16: | Line 15: | ||
Then <math>|a - b| = |2(2^2 + 4^2 + \ldots + 44^2) - 2(1^2 + 3^2 + 5^2 + \ldots 43^2) + 1^2 - 45^2 + 19|</math>. | Then <math>|a - b| = |2(2^2 + 4^2 + \ldots + 44^2) - 2(1^2 + 3^2 + 5^2 + \ldots 43^2) + 1^2 - 45^2 + 19|</math>. | ||
+ | We must now apply the formula <math>1^2 + 2^2 + \ldots + n^2 = \frac{n(n + 1)(2n + 1)}{6}</math>. From this formula, it follows that <math>2^2 + 4^2 + \ldots + (2n)^2 = \frac{2n(n + 1)(2n + 1)}{3}</math> and so that | ||
+ | :<math>1^2 + 3^2 + \ldots +(2n + 1)^2 = (1^2 + 2^2 + \ldots +(2n + 1)^2) - (2^2 + 4^2 + \ldots + (2n)^2)</math> | ||
+ | :<math>= \frac{(2n + 1)(2n + 2)(4n + 3)}{6} - \frac{2n(n + 1)(2n + 1)}{3} = \frac{(n + 1)(2n + 1)(2n + 3)}{3}</math>. Thus, | ||
− | + | <math>|a - b| = \left| 2\cdot \frac{44\cdot23\cdot45}{3} - 2\cdot \frac{22 \cdot 43 \cdot 45}{3} - 45^2 + 20\right| = |-25| = 025</math>. | |
− | + | Alternatively, rather than to use the formula for the sum of squares, notice that the difference between consecutive squares are consecutively increasing odd integers. | |
== See also == | == See also == | ||
− | + | {{AIME box|year=2005|n=I|num-b=11|num-a=13}} | |
− | |||
− | |||
[[Category:Intermediate Number Theory Problems]] | [[Category:Intermediate Number Theory Problems]] |
Revision as of 15:23, 4 March 2007
Problem
For positive integers let
denote the number of positive integer divisors of
including 1 and
For example,
and
Define
by
Let
denote the number of positive integers
with
odd, and let
denote the number of positive integers
with
even. Find
Solution
It is well-known that is odd if and only if
is a perfect square. (Otherwise, we can group divisors into pairs whose product is
.) Thus,
is odd if and only if there are an odd number of perfect squares less than
. So
and
are odd, while
are even, and
are odd, and so on.
So, for a given , if we choose the positive integer
such that
we see that
has the same parity as
.
It follows that the numbers between and
, between
and
, and so on, all the way up to the numbers between
and
have
odd, and that these are the only such numbers less than
(because
).
Thus .
Similarly, , where the
accounts for those numbers between
and
.
Then .
We must now apply the formula . From this formula, it follows that
and so that
. Thus,
.
Alternatively, rather than to use the formula for the sum of squares, notice that the difference between consecutive squares are consecutively increasing odd integers.
See also
2005 AIME I (Problems • Answer Key • Resources) | ||
Preceded by Problem 11 |
Followed by Problem 13 | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 | ||
All AIME Problems and Solutions |